Negative plate and battery
By adding fast ion conductors and setting grooves into the negative active layer of the lithium-ion battery, the problem of difficulty in taking into account both high capacity and high rate charge and discharge performance in the prior art is solved, and battery capacity improvement and high rate performance optimization are achieved.
Patent Information
- Application Number
- CN202411903513.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While increasing the capacity of the existing lithium-ion battery negative electrode materials, it is difficult to ensure the charging and discharging performance at high magnifications, and it is difficult to take into account both high capacity and high magnification charge and discharging performance.
Add a fast ion conductor to the negative electrode active layer and set up multiple spaced grooves. The fast ion conductor optimizes the transmission rate and path of lithium ions, and the groove increases the reaction area of the active substance and reduces the diffusion distance of lithium ions.
Effectively improve the battery capacity and high-rate charging and discharging performance, while reducing expansion rate and improving cycle stability, ensuring the stability and safety of the battery when outputting high power.
Smart Images

Figure CN119695075A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode sheet and a battery. Background Art
[0002] The negative electrode sheet is one of the key components of lithium-ion batteries, and its performance directly affects the overall electrochemical performance of lithium-ion batteries. The negative electrode sheet includes a negative current collector and a negative active layer on the surface of the negative current collector. The negative active layer is used to store and release lithium ions during the charge and discharge process. The negative active layer includes a negative electrode material, a conductive agent, and a binder. Graphite and silicon-based materials are the mainstream negative electrode materials for lithium-ion batteries at present. Among them, graphite has high mechanical stability and good cycle performance. It is relatively stable at high rates, which is conducive to the transmission of lithium ions, but its theoretical capacity is low. In contrast, the theoretical capacity of silicon-based materials can reach more than 10 times that of graphite, which can greatly increase the battery capacity. However, silicon undergoes large volume expansion and contraction during the charge and discharge process, which has a negative impact on the structural stability and electrochemical kinetics of the material, resulting in rapid capacity decay and decreased cycle performance during high-rate charge and discharge. While the existing negative electrode increases the capacity, it is difficult to ensure the charge and discharge performance at high rates, and it is difficult to achieve both high capacity and high-rate charge and discharge performance. Summary of the invention
[0003] The main purpose of the present application is to provide a negative electrode sheet and a battery to solve the problem in the related art that it is difficult to achieve both high capacity and high rate charge and discharge performance.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector; the surface of the negative electrode active layer away from the negative electrode current collector has a plurality of spaced grooves; the material of the negative electrode active layer comprises a negative electrode active material, a binder, a conductive agent and a fast ion conductor.
[0005] Furthermore, the materials of the negative electrode active layer include, by mass content: 90% to 97% of negative electrode active material, 2% to 5% of binder, 0.01% to 1.5% of conductive agent and 0.1% to 5% of fast ion conductor.
[0006] Further, the fast ion conductor includes at least one of an oxide electrolyte, a sulfide electrolyte, and a polymer electrolyte;
[0007] Preferably, the oxide electrolyte includes at least one of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium phosphorus oxynitride;
[0008] Preferably, the sulfide electrolyte includes at least one of a glass-ceramic sulfide electrolyte, a sulfide-germanite sulfide electrolyte, and a lithium-germanite sulfide electrolyte;
[0009] Preferably, the polymer electrolyte includes at least one of polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyacrylonitrile, and polyvinylidene fluoride.
[0010] Further, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or,
[0011] The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or,
[0012] The conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotube, and graphene;
[0013] Preferably, the negative electrode active material includes graphite and silicon carbon, wherein the mass ratio of graphite to silicon carbon is (6-9):(1-4).
[0014] Further, the ratio of the sum of the orthogonal projection areas S2 of the plurality of grooves on the negative electrode current collector to the orthogonal projection area S1 of the negative electrode active layer on the negative electrode current collector satisfies: 0.3≤S2 / S1≤0.8;
[0015] Furthermore, the shape of the positive projection of the groove on the side of the negative electrode current collector facing the negative electrode active layer is a long strip;
[0016] Preferably, the long side of the groove passes through the wide side of the negative electrode active layer, and the plurality of grooves are arranged at intervals along the length direction of the negative electrode sheet.
[0017] Furthermore, along the stacking direction of the negative electrode current collector and the negative electrode active layer, the thickness of the negative electrode active layer is H, the depth of the groove is d, and 10%≤d / H×100%≤50% is satisfied; and / or,
[0018] The width W of the groove is 10 to 100 μm; and / or,
[0019] The distance L between the center lines of any two adjacent grooves is 0.5 to 5.0 mm.
[0020] Furthermore, the groove is formed by laser etching; preferably, the power of the laser used for laser etching is ≥1800W, the actual output efficiency is 10% to 70%, and the processing speed is ≥28m / min.
[0021] Furthermore, the depth of the laser heat affected zone is ≤35 μm.
[0022] Furthermore, the thickness H of the negative electrode active layer is 30 to 50 μm;
[0023] The compaction density of the negative electrode active layer is 1.4-1.8 mg / cm 3 ;
[0024] The surface density of the negative electrode sheet is 60-300 mg / cm 2 .
[0025] According to another aspect of the present application, a battery is provided, comprising the negative electrode sheet provided in the first aspect.
[0026] By applying the technical solution of the present application, by adding a fast ion conductor in the negative electrode active layer and setting grooves, the fast ion conductor optimizes the transmission rate and path of lithium ions, and the setting of the grooves increases the reaction area of the active material and reduces the diffusion distance of lithium ions, thereby effectively improving the capacity of the battery and the charge and discharge performance at high rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the top view of the negative electrode sheet in one embodiment of the present application is shown;
[0028] Figure 2 A schematic diagram of the partial cross-sectional structure of a negative electrode sheet in one embodiment of the present application is shown.
[0029] Description of reference numerals:
[0030] 1-negative electrode current collector; 101-negative electrode active layer; 102-groove. DETAILED DESCRIPTION
[0031] As described in the background of this application, the battery in the prior art has the problem of being difficult to balance high capacity and high rate charge and discharge performance. In order to solve the above problem, the first aspect of this application provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector; the surface of the negative electrode active layer away from the negative electrode current collector has a plurality of grooves arranged at intervals; the material of the negative electrode active layer includes a negative electrode active material, a binder, a conductive agent and a fast ion conductor.
[0032] Providing grooves on the surface of the negative electrode active layer can, firstly, significantly increase the contact area with the electrolyte, promote the penetration of the electrolyte, and enable more active substances to participate in the electrochemical reaction, thereby improving the capacity and energy density of the battery; secondly, the groove structure provides a shorter transmission path for lithium ions, especially under high-rate charge and discharge conditions, reduces the diffusion distance of lithium ions from the electrolyte to the inside of the active substance, optimizes the diffusion kinetics of lithium ions, and improves the rate performance of the battery; at the same time, the grooves can help alleviate the stress caused by the volume expansion and contraction of the active substance during the charge and discharge process, thereby improving the structural stability and cycle life of the negative electrode material; in addition, the grooves help to evenly distribute the electrolyte in the active material layer, reduce the local bottleneck of lithium ion transmission, make the electrochemical reaction more uniform, avoid local overheating and the generation of side reactions, and improve the safety and reliability of the battery.
[0033] Therefore, by setting the grooves, the electrochemical performance of the battery can be improved from four aspects: increasing the effective surface area, improving the lithium ion diffusion path, enhancing the mechanical stability, and promoting the uniform distribution of the electrolyte.
[0034] Fast ion conductors refer to substances that can efficiently transfer lithium ions within the material. First, fast ion conductors have high lithium ion conductivity and can significantly accelerate the transfer rate of lithium ions in the negative electrode active layer. This not only improves the efficiency of the charge and discharge process, but also enhances the rate performance of the battery, that is, it can still maintain a high capacity and energy density at high current density; secondly, the introduction of fast ion conductors optimizes the diffusion path of lithium ions in the negative electrode active layer, reduces kinetic barriers, and makes the insertion and deinsertion process of lithium ions smoother, even during rapid charge and discharge, it can maintain good electrochemical reaction activity and extend the cycle life of the battery; in addition, fast ion conductor materials also have high electronic conductivity. They can act as a bridge for electron transmission and improve the conductive network of the negative electrode active layer, thereby improving the conductivity of the entire negative electrode sheet and ensuring the stability and safety of the battery at high power output.
[0035] Therefore, by adding a fast ion conductor to the negative electrode active layer, the electrochemical performance of the battery can be improved from three aspects: enhancing lithium ion transport, improving electrochemical reaction kinetics, and increasing conductivity.
[0036] By adding a fast ion conductor and providing a groove in the negative electrode active layer, the present application can effectively improve the capacity and high-rate charge and discharge performance of the battery without sacrificing the cycle life and safety of the battery, and can also take into account reducing the expansion rate and improving the cycle stability.
[0037] The materials of the negative electrode active layer include, by mass content, 90% to 97% of negative electrode active material, 2% to 5% of binder, 0.01% to 1.5% of conductive agent and 0.1% to 5% of fast ion conductor. By limiting the proportion of each material in the negative electrode active layer, the capacity and high rate charge and discharge performance can be further improved.
[0038] Among them, the mass content of the negative electrode active material in the negative electrode active material layer is 90% to 97%, for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or a range consisting of any two thereof; the mass content of the binder in the negative electrode active material layer is 2% to 5%, for example, 2%, 3%, 4%, 5% or a range consisting of any two thereof; the mass content of the conductive agent in the negative electrode active material layer is 0.01% to 1.5%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 1%, 1.2%, 1.5% or a range consisting of any two thereof; the mass content of the fast ion conductor in the negative electrode active material layer is 0.1% to 5%, for example, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two thereof.
[0039] In some embodiments, the fast ion conductor includes at least one of an oxide electrolyte, a sulfide electrolyte, and a polymer electrolyte.
[0040] Specifically, the oxide electrolyte is a compound containing lithium and other components (phosphorus, titanium, aluminum, lanthanum, germanium, zinc, zirconium), which can be divided into crystalline and amorphous states. Exemplarily, the oxide electrolyte includes at least one of lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium titanium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium phosphorus oxynitride. The above oxide electrolyte has high lithium ion conductivity and good chemical stability.
[0041] The sulfide electrolyte is mainly composed of sulfide. Exemplarily, the sulfide electrolyte includes at least one of a glass-ceramic sulfide electrolyte, an argyrodite sulfide electrolyte, and a lithium-germanite sulfide electrolyte.
[0042] Specifically, according to the different crystal structures, sulfide electrolytes can be divided into glass-ceramic type crystal, argyrodite crystal, and lithium-germanite crystal. Among them, the chemical formula of glass-ceramic sulfide electrolyte can be Li2S-M x S y , refers to the process of combining lithium sulfide (Li2S) with transition metal sulfide (M x S y) are mixed under appropriate conditions, M refers to one or more transition metals, such as phosphorus (P), germanium (Ge), tin (Sn), etc., and x and y represent the stoichiometric ratio of the transition metal and the sulfur in the sulfide. The chemical formula of the argyrodite-type sulfide electrolyte can be Ag8GeS6. The lithium-germanite-type sulfide electrolyte can be, for example, Li 10 5P 12 Or Li6PS5X (where X can be Cl, Br or I). The ionic conductivity of the above sulfide electrolytes is generally higher than that of oxide electrolytes, which can further improve the capacity of the battery and the charge and discharge performance at high rates.
[0043] The polymer electrolyte is flexible and processable, can adapt to the mechanical stress changes inside the battery, can further reduce the expansion rate and improve the cycle stability of the battery. Exemplarily, the polymer electrolyte includes at least one of polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyacrylonitrile, and polyvinylidene fluoride.
[0044] The present application does not limit the specific types of negative electrode active materials, binders and conductive agents. For example, in some embodiments, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or the conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fibers, carbon nanotubes, and graphene.
[0045] In some embodiments, the negative electrode active material includes graphite and silicon carbon. By mixing graphite and silicon carbon in a specific ratio, the specific capacity of the negative electrode can be significantly improved while ensuring a certain degree of cycle stability, thereby improving the energy density of the entire battery. The stability of graphite can also be used to mitigate the impact of silicon volume expansion and improve the cycle stability of the composite material. In addition, the overall conductive network of the negative electrode material can be improved, which helps to improve the rate performance of the battery, that is, the ability to charge and discharge quickly.
[0046] In some embodiments, the mass ratio of graphite to silicon carbon is (6-9):(1-4). By limiting the mass ratio of graphite to silicon carbon to (6-9):(1-4), the capacity and energy density of the battery can be significantly improved while maintaining a certain cycle stability and safety. Through the appropriate proportion of compounding, the high capacity advantage of silicon is brought into play, and the stability and conductivity of graphite are used to achieve a balance between performance and stability.
[0047] The mass ratio of graphite to silicon carbon is (6-9):(1-4), for example, 6:4, 7:3, 8:2, 9:1 or a range consisting of any two thereof.
[0048] When preparing the negative electrode sheet, the negative electrode active material, conductive agent, binder and fast ion conductor can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. The material of the negative electrode current collector can be at least one of copper foil, nickel foam and copper foam.
[0049] In some embodiments, the ratio of the sum of the positive projection areas S2 of the plurality of grooves on the negative electrode current collector to the positive projection area S1 of the negative electrode active layer on the negative electrode current collector satisfies: 0.3≤S2 / S1≤0.8. By limiting the area ratio of the grooves, it is ensured that there is sufficient groove area to improve the penetration of the electrolyte and the kinetic performance of lithium ions, while avoiding excessive reduction of the effective active material area due to excessive groove area, thereby affecting the overall capacity of the battery. In this way, sufficient capacity is maintained and the charge and discharge rate performance and cycle stability of the battery are significantly improved.
[0050] In some embodiments, the positive projection of the groove on the side of the negative electrode current collector facing the negative electrode active layer is in the shape of a long strip. The long strip groove can serve as a path for electrolyte penetration, ensuring that the electrolyte can evenly and deeply contact all parts of the negative electrode active layer, and can also promote the diffusion of lithium ions and reduce the resistance of lithium ion transmission, thereby improving the rate performance and kinetic behavior of the battery; in addition, the long strip groove can serve as a stress release channel to reduce the stress accumulation caused by the volume change of the active material during the charge and discharge process of the battery, which helps to improve the mechanical stability and cycle life of the electrode.
[0051] In some embodiments, the long side of the groove runs through the wide side of the negative electrode active layer, and multiple grooves are arranged at intervals along the length direction of the negative electrode sheet. In this way, the long axis of the groove is parallel to the width direction of the negative electrode active layer, and the groove runs through the edge of the negative electrode active layer, which allows the electrolyte to penetrate into the active material faster, improves the efficiency and speed of the electrochemical reaction, and further increases the contact area between the active material and the electrolyte, so that more active materials participate in the electrochemical reaction, which helps to improve the capacity and energy density of the battery.
[0052] This application does not limit the specific size of the groove, which can be adjusted according to actual conditions. In some embodiments, along the stacking direction of the negative electrode current collector and the negative electrode active layer, the thickness of the negative electrode active layer is H, and the depth of the groove is d, satisfying 10% ≤ d / H × 100% ≤ 50%; and / or, the width W of the groove is 10 to 100 μm; and / or, the spacing L between the center lines of any two adjacent grooves is 0.5 to 5.0 mm. Appropriate groove size and distribution can improve the permeability of the electrolyte and increase the lithium ion diffusion path while maintaining the integrity and stability of the electrode structure. By limiting the parameters such as the depth, width and spacing of the groove within the above range, the battery performance can be optimized.
[0053] The groove can be formed by laser etching, mechanical grooving, chemical etching, etc. In some embodiments, the groove is formed by laser etching. Laser etching can avoid material damage and contamination caused by mechanical cutting, ensure the smoothness and cleanliness of the groove edge, and help improve battery performance and reliability.
[0054] Laser etching technology can adjust parameters according to the needs of grooves of different shapes and sizes. In some embodiments, the power of the laser used for laser etching is ≥1800W, the actual output efficiency is 10% to 70%, and the processing speed is ≥28m / min. By limiting the parameters of laser etching, efficient, accurate and high-quality preparation of grooves can be achieved, thereby optimizing the energy density, charge and discharge rate performance and cycle stability of the battery, while also achieving fine cutting and reducing the width of the heat-affected zone.
[0055] Specifically, a laser power of ≥1800W means that it can provide enough energy to ensure the efficiency and accuracy of the cutting process. High-power lasers can quickly heat and vaporize materials to form high-quality grooves without causing unnecessary thermal damage to surrounding materials. The actual output efficiency is defined as the percentage of the actual output power to the laser power. The processing speed refers to the size processed per unit time. A processing speed of ≥28m / min indicates the rapidity of laser etching, which helps to improve production efficiency.
[0056] During the laser etching process, the area where the negative electrode active layer is affected by the laser thermal energy and undergoes changes in microstructure, physical properties or chemical properties is called the laser heat affected zone. The depth of the laser heat affected zone generally refers to the dimension perpendicular to the laser scanning direction, that is, the size of the area where the material properties change along the thickness direction of the negative electrode active layer. In some embodiments, the depth of the laser heat affected zone is ≤35μm, which indicates that laser etching technology can accurately control the size of the heat affected zone to avoid negative impacts on the performance of the electrode material.
[0057] In some embodiments, the thickness H of the negative electrode active layer is 30-50 μm. The negative electrode current collector has two functional surfaces arranged opposite to each other, which are used to arrange the negative electrode active layer. The thickness H of the negative electrode active layer refers to the thickness of the negative electrode active layer on one side of the negative electrode current collector.
[0058] In some embodiments, the compaction density of the negative electrode active layer is 1.4 to 1.8 mg / cm 3 The compaction density refers to the amount of active material that can be contained within a unit volume. By limiting the compaction density of the negative electrode active layer to the above range, the active material can be packed more densely, which helps to achieve a higher capacity.
[0059] In some embodiments, the surface density of the negative electrode sheet is 60 to 300 mg / cm 2 . Surface density refers to the mass per unit area of the active material coated on both sides of the negative electrode sheet. By limiting the surface density of the negative electrode sheet within the above range, it is possible to ensure that the energy density of the battery is high enough, optimize the lithium ion transmission path and electronic conductivity, and also help control the expansion of the battery during charging and discharging, reduce stress accumulation during the cycle process, and thus improve the cycle stability of the battery.
[0060] A second aspect of the present application provides a battery, comprising the negative electrode sheet provided in the first aspect.
[0061] Due to the inclusion of the above-mentioned negative electrode sheet, the battery not only has high capacity and low expansion rate, but also has excellent charge and discharge performance at a high rate.
[0062] In some embodiments, the battery further includes a positive electrode sheet, a separator, and an electrolyte.
[0063] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer arranged on the surface of the positive electrode current collector.
[0064] When preparing the positive electrode sheet, the positive electrode active material, the second conductive agent, and the second binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the positive electrode active layer includes 70% to 99% of the positive electrode active material, 0.5% to 15% of the second conductive agent, and 0.5% to 15% of the second binder in terms of mass percentage.
[0065] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the second conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the second binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0066] The present application does not limit the specific type of the positive electrode active material in the positive electrode sheet, and it can be a positive electrode active material commonly used in current batteries, such as at least one composite oxide of lithium and metals of cobalt, nickel, manganese and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium-rich manganese, nickel-cobalt lithium manganese oxide, lithium manganese oxide, and lithium iron phosphate.
[0067] The battery also includes a diaphragm. The present application does not limit the specific selection of the diaphragm material, and it can be a diaphragm material commonly used in batteries, such as a polypropylene diaphragm, a polyethylene diaphragm, a polypropylene / polyethylene double-layer composite diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite diaphragm, etc.
[0068] When preparing the battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain the battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte is injected into the dry battery. After the battery is aged, formed and sealed for the second time, the battery preparation is completed.
[0069] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0070] Example 1
[0071] The method for preparing the negative electrode sheet of this embodiment includes:
[0072] The negative electrode active material, binder, conductive agent and fast ion conductor are mixed in a mass ratio of 95%:3.5%:1.0%:0.5%, and 50% of the total mass of water is added and stirred to form a negative electrode slurry, wherein the negative electrode active material is a mixture of graphite and silicon carbon in a mass ratio of 8:2, the binder is polyacrylic acid PAA and styrene-butadiene rubber SBR, the conductive agent is conductive carbon black SP and carbon nanotubes CNT, and the fast ion conductor is lithium aluminum titanium phosphate LATP; the negative electrode slurry is coated on a copper foil current collector with a thickness of 6 μm, and the double-sided coating surface density is 100 g / m 2After cold pressing and vacuum drying, a negative electrode sheet with a thickness of 72 μm was obtained. Figure 1 and Figure 2 As shown, the thickness H of the single-side negative electrode active layer 101 is 33 μm, and the surface of the negative electrode active layer 101 away from the negative electrode current collector 1 is laser etched to form a groove 102 to obtain a negative electrode sheet; wherein the groove 102 is a parallel line, the depth d of the groove 102 is 10.8 μm, the width W is 80 μm, the spacing L between the center lines of any two adjacent grooves 102 is 2 mm, the power of the laser used for laser etching is 2000 W, the actual output efficiency is 60%, the processing speed is 40 m / min, and the depth of the heat affected zone is 15 μm.
[0073] Example 2
[0074] The difference from Example 1 is that the fast ion conductor added to the negative electrode active layer is lithium germanium sulfide LGPS electrolyte.
[0075] Example 3
[0076] The difference from Example 1 is that the fast ion conductor added to the negative electrode active layer is a polyethylene oxide electrolyte.
[0077] Example 4
[0078] The difference from Example 1 is that the mass ratio of graphite to silicon carbon is 9:1.
[0079] Example 5
[0080] The difference from Example 1 is that the mass ratio of graphite to silicon carbon is 7:3.
[0081] Example 6
[0082] The difference from Example 1 is that the negative electrode active material is graphite.
[0083] Example 7
[0084] The difference from Example 1 is that the negative electrode active material is silicon carbon.
[0085] Example 8
[0086] The difference from Example 1 is that the depth d of the groove is 3 μm.
[0087] Example 9
[0088] The difference from Example 1 is that the depth d of the groove is 16.5 μm.
[0089] Example 10
[0090] The difference from Example 1 is that the width W of the groove is 10 μm.
[0091] Embodiment 11
[0092] The difference from Example 1 is that the width W of the groove is 100 μm.
[0093] Example 12
[0094] The difference from Example 1 is that the distance L between the center lines of any two adjacent grooves is 0.5 mm.
[0095] Example 13
[0096] The difference from Example 1 is that the distance L between the center lines of any two adjacent grooves is 5 mm.
[0097] Comparative Example 1
[0098] The difference from Example 1 is that the negative electrode active layer is not subjected to laser etching, that is, no groove is provided.
[0099] Comparative Example 2
[0100] The difference from Example 1 is that no fast ion conductor is added to the negative electrode active layer.
[0101] Test example
[0102] 1. Capacity and cycle stability test
[0103] Large single crystal nickel cobalt lithium manganese oxide (NCM523) is mixed with conductive carbon black and PVDF in a mass ratio of 94:3.0:3.0, dissolved in N-methylpyrrolidone, and the solid content is controlled to be 50% to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil current collector, and after vacuum drying at 95° C., roller pressing, and pressurizing, a positive electrode sheet is obtained;
[0104] The negative electrode sheet, separator and positive electrode sheet of the embodiment and the comparative example are assembled into a lithium-ion battery, and the electrolyte is injected to obtain a soft-pack battery of about 400mAh; wherein the electrolyte is 1mol / L LiPF6 / ethylene carbonate (EC) + propylene carbonate (PC) + diethyl carbonate (DEC) + EMC (volume ratio 1:0.3:1:1), and the separator is a PP / PE / PP three-layer composite separator.
[0105] The above soft pack battery was used to test the cycling performance of the material. It was charged to 4.20V at a constant current of 3C, then charged at a constant voltage, the current gradually decreased to 0.05C, and then discharged to 2.75V at a discharge rate of 1C. This charge and discharge cycle was repeated 500 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q500 at the 500th cycle were measured. The 500-week capacity retention rate was calculated according to the 500-week capacity retention rate = Q500 / Q1×100%.
[0106] 2. 2C charging constant current ratio
[0107] The above soft pack battery was charged at 25°C with a constant current of 2C to 4.20V, and then charged at a constant voltage with the current gradually reduced to 0.05C. The charging capacity of the 2C charging stage and the total charging capacity of the entire charging process were recorded. The total charging capacity should include the charging capacity of the 2C constant current charging stage and the subsequent constant voltage charging stage.
[0108] The 2C charging constant current ratio can be calculated by the following formula: 2C charging constant current ratio = 2C constant current charging capacity / total charging capacity × 100%.
[0109] 3. Expansion rate test
[0110] The initial thickness of the battery of the test example and the comparative example is d1, and the thickness of the battery after the cycle is d2. The above battery is charged to 4.50V at a constant current of 3C at 25°C, then charged to 4.50V at a constant voltage of 0.05C, and then discharged to 3.0V at a discharge rate of 1C. This charge and discharge cycle is repeated 500 times, and the thickness of the battery after 500 cycles is d2. The expansion rate is calculated according to the expansion rate = (d2-d1) / d1×100%.
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114] According to Table 1, the embodiments of the present application are superior to the comparative examples in terms of capacity utilization, charge-constant current ratio, cycle and other performances. It can be seen that applying the negative electrode sheet of the present application to the battery can effectively improve the capacity and high-rate charge and discharge performance.
[0115] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A negative electrode sheet, characterized in that: It comprises a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector; the surface of the negative electrode active layer away from the negative electrode current collector has a plurality of spaced grooves; the material of the negative electrode active layer comprises a negative electrode active material, a binder, a conductive agent and a fast ion conductor.
2. The negative electrode sheet according to claim 1, characterized in that: The materials of the negative electrode active layer include, by mass content, 90% to 97% of negative electrode active material, 2% to 5% of binder, 0.01% to 1.5% of conductive agent and 0.1% to 5% of fast ion conductor.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The fast ion conductor includes at least one of an oxide electrolyte, a sulfide electrolyte, and a polymer electrolyte; Preferably, the oxide electrolyte comprises at least one of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium phosphorus oxynitride; Preferably, the sulfide electrolyte includes at least one of a glass-ceramic sulfide electrolyte, a sulfide-germanite sulfide electrolyte, and a lithium-germanite sulfide electrolyte; Preferably, the polymer electrolyte includes at least one of polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyacrylonitrile and polyvinylidene fluoride.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or, The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or, The conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotube, and graphene; Preferably, the negative electrode active material includes graphite and silicon carbon, wherein the mass ratio of the graphite to the silicon carbon is (6-9):(1-4).
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The ratio of the sum S2 of the orthogonal projection areas of the plurality of grooves on the negative electrode current collector to the orthogonal projection area S1 of the negative electrode active layer on the negative electrode current collector satisfies: 0.3≤S2 / S1≤0.
8.
6. The negative electrode sheet according to claim 5, characterized in that: The shape of the orthographic projection of the groove on the side of the negative electrode current collector facing the negative electrode active layer is a long strip; Preferably, the long side of the groove passes through the wide side of the negative electrode active layer, and a plurality of the grooves are arranged at intervals along the length direction of the negative electrode sheet.
7. The negative electrode sheet according to claim 6, characterized in that: Along the stacking direction of the negative electrode current collector and the negative electrode active layer, the thickness of the negative electrode active layer is H, the depth of the groove is d, and 10%≤d / H×100%≤50% is satisfied; and / or, The width W of the groove is 10 to 100 μm; and / or, The distance L between the center lines of any two adjacent grooves is 0.5-5.0 mm.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The groove is formed by laser etching; preferably, the power of the laser used for the laser etching is ≥1800W, the actual output efficiency is 10% to 70%, the processing speed is ≥28m / min, and the depth of the laser heat-affected zone is ≤35μm.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The thickness H of the negative electrode active layer is 30 to 50 μm; and / or, The compaction density of the negative electrode active layer is 1.4 to 1.8 mg / cm 3 and / or, The surface density of the negative electrode sheet is 60 to 300 mg / cm 2 .
10. A battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 9.
Citation Information
Patent Citations
Negative electrode comprising solid electrolyte and low porosity and lithium battery applying the negative electrode
CN109659493A
Battery pole piece, secondary battery and device
CN117276465A
Battery
CN118352477A
Battery
CN118538863A
Lithium ion battery and electronic equipment
CN118888820A